ANALISIS PENGARUH SEKTOR PERTANIAN DAN SEKTOR INDUSTRI TERHADAP KESEMPATAN KERJA DI KABUPATEN/KOTA PROVINSI JAMBI - Aliya Nafsah; Zulgani; Erni Achmad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study is to analyze how the agricultural and industrial sectors affect employment opportunities in the districts/cities of Jambi Province between 2017 and 2024. Data were taken from the Central Statistics Agency (BPS) and covered the GRDP of the agricultural and industrial sectors, as well as the number of people employed in the agricultural and industrial sectors. The analysis was conducted using a panel data regression method using a Fixed Effects Model. The research findings indicate that both sectors simultaneously have a significant influence on employment opportunities. However, separately, the agricultural sector shows a significant negative effect on employment opportunities, meaning that the increase in GRDP in the agricultural sector is not accompanied by an increase in the number of workers. On the other hand, the industrial sector has a significant positive influence, which shows that industrial development is able to absorb labor in Jambi Province.